DETERMINATION OF THE LEAD CONTENT IN SPINACH BY UTILIZATION OF THE POTENTIOMETRIC STRIPPING ANALYSIS (PSA) - Babincev, Lj.; Rajkovic, Lj. (Journal of Engineering & Processing Management, 2010)
Absorption of elements by plants is regulated with a series of factors that depend on the plant in issue and conditions of living environment. The main factor that controls the mineral content in plants is a genetic potential for sustenance with different minerals. It is being exhibited with unequal sensitivity and ability for accumulation of specific elements. Particularity of species and genotypes with regard the mineral sustenance originates from their adjustment to specific ecological conditions, particularity related to metabolism, morphological and anatomic structure. A plant’s ability to absorb microelements depends on morphology of its root, which has three major functions: connecting the plant to its surface, absorption and transport of substance and water, synthesis of phytohormones and other organic compounds. In addition to its role in inclusion of elements from the ground, the root doubles as a fairly good filter. Essential elements pass through the root barrier easily, straightforwardly advancing to the upper parts of a plant while still being mobile, whereas toxic elements are withheld, unless their presence is in ample concentrations. It is known that the root epidermis represents a barrier for lead absorption. Zinc has a distinctively large mobility through the plant and minor accretion in the root. While toxic and physiologically unnecessary for any plant, cadmium advances rapidly towards the upper parts. Since lead has the worst mobility towards the upper parts of the plant, taking into consideration its high toxicity levels if it becomes the food chain constituent, this report elaborates determination of the lead content in spinach leaves. This determination of the lead content was conducted by utilization of the Potentiometric Stripping Analysis (PSA).The Potentiometric Stripping Analysis (PSA) is an electroanalytic highly sensitive method for determining the content of many heavy metals. Examining of sensitivity threshold and linearity range was conducted prior to this measurement.